Spleenic Lymphoma and Hemoperitoneum in Jersey Bull: Clinical and Pathological Aspects - Sampaio, Paulo Henrique; Fidelis Junior, Otávio Luiz; Moreira, Pamela Rodrigues Reina; Rodrigues, Lúcia Helena; Cadioli, Fabiano Antonio; Vasconcelos, Rosemeri de Oliveira; Marques, Luiz Carlos (Brazilian Journal of Veterinary Pathology, 2014)
Lymphoma is the most prevalent neoplasia in dairy cattle. The etiology can be viral in animals affected by bovine leukemia virus (BLV) or be classified as primary. Lymphoma can affect several organs and according to the system involved, the clinical signs could manifest themselves in different ways. These tumors can be classified through macroscopic characteristics, histology and immunostaining. This classification can be used to predict prognosis and response to therapy. The aim of this case report was to immunostain and classify the tumor, for which anti-CD4, anti-CD8, anti-CD79 and anti-CD3 markers were used in addition to histopathological findings, in order to classify the tumor. The tumor was positive only for anti-CD3 marker, indicating that it is a tumor of young cells and, in association with histopathology and hematological data, it can be concluded that spleen neoplasia is lymphocytic lymphoma originated from a lymphocytic leukemia.